The mathematician's brain - Ruelle, David (Princeton University Press, 2007)
The Mathematician's Brain poses a provocative question about the world's most brilliant yet eccentric mathematical minds: were they brilliant because of their eccentricities or in spite of them? In this book, David Ruelle, the mathematical physicist who helped create chaos theory, gives us an insider's account of the celebrated mathematicians he has known-their quirks, oddities, personal tragedies, bad behavior, descents into madness, tragic ends, and the sublime, inexpressible beauty of their most breathtaking mathematical discoveries. Ruelle holds nothing back in his revealing and deeply personal reflections on mathematicians such as Alan Turing, Alexander Grothendieck, Rene Thom, Bernhard Riemann, and Felix Klein. Each chapter examines an important mathematical idea and the visionary minds behind it. Ruelle explores the philosophical issues raised by each, offering insights into the truly unique and creative ways mathematicians think and showing how the mathematical setting is most favorable for asking philosophical questions about meaning, beauty, and the nature of reality.